Theory of Planned Behavior and Ethics Theory in Digital Piracy: An Integrated Model - Yoon, Cheolho (2011)
Since digital piracy has posed a significant threat to the development of the software industry and the growth of the digital media industry, it has, for the last decade, held considerable interest for researchers and practitioners. This article will propose an integrated model that combines the theory of planned behavior (TPB) and ethics theory, the two theories that are most often used in digital piracy studies. Data were obtained from university students in China, and the model was examined using the structural equation model (SEM). The results show that moral obligation and justice, derived from ethics theories and TPB variables, such as attitude, subjective norms, and perceived behavioral control, influence the behavioral intentions of individuals to commit digital piracy. The attitude of individuals toward digital piracy is also found to be influenced by perceived benefits, perceived risk, and habit.
Keywords: Habit; Perceived risk; perceived benefits; Justice; Moral Obligation; ethics theory; theory of planned behavior; Digital piracy